Enhancing the Effect of Placental Extract on the Regeneration of Crush Injured Facial Nerve - Lim, Gyeong Min; Cho, Gwang-Won; Ganesan, Chitra Devi; Choi, Ji Hyun; Ang, Mary Jasmin; Moon, Changjong; Jang, Chul Ho (Experimental neurobiology, 2022)
There is a scarcity of experimental studies on peripheral nerve regeneration using placental extract (PE). This study aimed to investigate the effects of topical PE application on recovery after crush injury to the rat facial nerve using functional, electrophysiological, and morphological evaluations. The viability of the RSC96 Schwann cells treated with PE (0.5~4 mg/ml) increased significantly. Immunoblot test revealed that PE application enhanced the migration of RSC96 cells. Quantitative polymerase chain reaction demonstrated that PE increased the expression of neurotropic genes. The recovery from vibrissa fibrillation in the PE-treated group was superior to that in the control group. The threshold of action potential was also significantly lower in the PE group. Histopathological examination showed that crushed facial nerves treated with PE exhibited larger axons. The surrounding myelin sheaths were more distinct and thicker in the PE-treated group. Hence, PE may be considered a topical therapeutic agent for treating traumatic facial nerve paralysis.